2006
DOI: 10.1084/jem.20061775
|View full text |Cite
|
Sign up to set email alerts
|

Th17 functions as an osteoclastogenic helper T cell subset that links T cell activation and bone destruction

Abstract: In autoimmune arthritis, traditionally classified as a T helper (Th) type 1 disease, the activation of T cells results in bone destruction mediated by osteoclasts, but how T cells enhance osteoclastogenesis despite the anti-osteoclastogenic effect of interferon (IFN)-γ remains to be elucidated. Here, we examine the effect of various Th cell subsets on osteoclastogenesis and identify Th17, a specialized inflammatory subset, as an osteoclastogenic Th cell subset that links T cell activation and bone resorption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
708
1
21

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,353 publications
(749 citation statements)
references
References 53 publications
19
708
1
21
Order By: Relevance
“…GM-CSF and IL-4 from Th2 cells also inhibit osteoclastogenesis and induce type 2 macrophages (M2) that refrain inflammatory responses and promote tissue remodeling [1,38,39]. In contrast, IL-17 from Th17 cells facilitates osteoclastogenesis by promoting chronic inflammation in microenvironments [40]. Ultimately, the fate of monocytes/macrophages may be determined by the net effects of cytokines and various membranous proteins, including 4-1BB.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF and IL-4 from Th2 cells also inhibit osteoclastogenesis and induce type 2 macrophages (M2) that refrain inflammatory responses and promote tissue remodeling [1,38,39]. In contrast, IL-17 from Th17 cells facilitates osteoclastogenesis by promoting chronic inflammation in microenvironments [40]. Ultimately, the fate of monocytes/macrophages may be determined by the net effects of cytokines and various membranous proteins, including 4-1BB.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that CD4+ Th1 cells are central to the cell-mediated immunity events associated with the disease, particularly through interferon-γ production, is now challenged by the discovery of the interleukin-17-producing Th17 population [10]. Although it has been proposed that Th17 cells confer specific osteoclast-inducing activity [11], their preceise role in periodontitis is still unclear. On the molecular level, the process of bone resorption is determined by the interplay of members of the tumor necrosis factor (TNF) ligand and receptor families [12].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, studies in a murine experimental arthritis model showed that IL-17 was involved in both the initiation and the progression of the disease. Furthermore, elevated levels of IL-17 were detected in synovial fluid from patients with rheumatoid arthritis, and osteoclast formation was inhibited by anti-IL-17 antibody, suggesting an effect on bone resorption (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%